Quality of Service control for interactive real-time applications - Tan, Teong Yee. (2008)
In this thesis, a set of two QoS control schemes — a packet scheduling scheme and an adaptive admission control scheme — are proposed to achieve end-to-end QoS for interactive real-time applications with good network resource utilization. The proposed scheduling scheme dynamically adjusts the resources allocated to different applications based on the perceived QoS performance and the desired QoS performance. When combined with the proposed adaptive admission control scheme, the scheduling scheme provides an end-to-end delay bound and packet loss control for interactive real-time applications.